Towards a cultural politics of climate change devices, desires and dissent - Bulkeley, Harriet 1972-; Paterson, Matthew 1967-; Stripple, Johannes (Cambridge University Press, 2016)
Towards a Cultural Politics of Climate Change provides a new perspective on how climate change matters in policy-making, business and everyday life. It argues that the work of low carbon transitions takes place through the creation of devices, the mobilisation of desires, and the articulation of dissent. Using case studies from the US, Australia, and Europe, the book examines the creation and contestation of new forms of cultural politics - of how a climate-changed society is articulated, realized and contested. Through this approach it opens up questions about how, where and by whom climate politics is conducted and the ways in which we might respond differently to this societal challenge. This book provides a key reference point for the emerging academic community working on the cultural politics of climate change, and a means through which to engage this new area of research with the broader social sciences